Implementasi Kebijakan Sistem Informasi Pegawai Daerah (Sipd) Berdasarkan Perpres Nomor 95 Tahun 2018 : Studi Pada BKPSDM Kota Palembang - Tony Mirza (Komsospol, 2021)
The purpose of this study is knowing how to implement the Regional Personnel Information System (SIPD) policy and knowing the elements that can support and hinder the implementation of the SIPD strategy at the Agency for Development of Personnel and Human Resources (BKPSDM) Palembang City. This exploration is directed by a subjective methodology. Exploration is directed at the Palembang City BKPSDM. Judging from the consequences of the review, it tends to be reasonable that the implementation of the SIPD Policy which was completed at the Palembang BKPSDM as a whole has been carried out very well. However, in carrying out the SIPD strategy there are several obstacles, including the proposed increase in ASN/representatives which seems to make it difficult for workers with an excessive number of stages, especially through OPD, BKPSDM, later at that time BKN. These stages may not have to be passed, considering that only by using the SIPD application all information on labor regulations can be obtained at OPD, BKPSDM and BKN without the need for the relevant representative to take care of it to the regions. Variables that affect the implementation of this SIPD strategy include correspondence factors, assets, behavior and regulatory design